Optimization of Food Composition for Hypertensive Patient using Variable Neighborhood Search - Aprilia Nur Fauziyah; Wayan Firdaus Mahmudy (Institute of Advanced Engineering and Science, 2017)
Hypertension is a major symptom that cause other diseases appear such as non-communicable diseases, cancer, and diabetes if the nutrients on hypertensive patients not controlled from the actual nutrition need. One of healthy life effort for the patients is consuming healthy food that considers level of salt in the foods. The problem to determine the food composition that considers level of salt and minimum cost of the food is solved using Variable Neighborhood Search. This study compares 3 neighborhood structures: insertion, exchange, and 2-opt. The use of 2-opt neighborhood structure gives the highest fitness averages of other neighborhood structure. Selection and arrangement of neighborhood structure in every k neighborhood have effect on the solution is obtained. The result of this study contains composition of foods with nutrients which are close to the needs of hypertension patients with attentions the sodium and minimal cost within a day.